KEPEMIMPINAN MEMODERASI PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KERJA TERHADAP KINERJA GURU (Studi pada guru SD Negeri di UPTD Pendidikan Kecamatan Genuk kota Semarang) - Astuti, Anik (Students Journal of Economic and Management, 2012)
This study aims to examine and analyze leadership moderating the influence of work motivation and work discipline to teacher performance at state elementary school of UPTD Genuk Regency in Semarang City with leadership as moderating variable. The populations of the study were 217 teachers, while the samples were 148 people as respondents using Kracjie and Morgan method. Sampling technique used purposive proposional sampling. Analyses requirement test used normality and multicolinierity test. Model test used determinant coefficient and F test (Goodness of Fit). Hipotesis test used t test. The results show that: Â work motivation has positive and significant impact to teacher performance, Â work disciplineÂ  has positive and significant impact to teacher performance, Â leadership has positive and significant impact to teacher performance, leadership doesnât moderate the influence of work motivation to teacher performance, Â leadership moderates the influence of work discipline to teacher performance. Key words: work motivation, work discipline, leadership and teacher performance.